Integrated Transcriptome Analysis of Iris Tissues in Experimental Autoimmune Uveitis - Li, Dan; Huang, Chang; Han, Xiaoyan; Sun, Jianguo (Frontiers in Genetics, 2022)
Uveitis is a severe ocular inflammatory disease that affects the uvea and frequently results in visual impairment, even irreversible blindness. The current treatments for uveitis have exhibited adverse side effects. To find novel targets of this disease, we perform comparative transcriptome analysis using normal (n = 4) and experimental autoimmune uveitis (EAU) (n = 4) rat iris samples. We mainly focus on the expression profiles of mRNAs and long non-coding RNAs, and identify NOD-like receptor signaling pathway as the one that plays a key role in the pathological changes of the EAU irises. Our work demonstrates that the EAU iris transcriptome can be mined to uncover novel targetable pathways for uveitis. The molecules in NOD-like receptor signaling pathway could be novel therapeutic targets for autoimmune uveitis.